Repetitively pulsed Fe: ZnSe laser with an average output power of 20 W at room temperature of the polycrystalline active element. (May 2017) - Velikanov, S.D.; Gavrishchuk, E.M.; Zaretsky, N.A.; Zakhryapa, A.V.; Ikonnikov, V.B.; Kazantsev, S.Yu.; Kononov, I.G.; Maneshkin, A.A.; Mashkovskii, D.A.; Saltykov, E.V.; Firsov, K.N.; Chuvatkin, R.S.; et al.
Abstract: The energy and spectral-temporal characteristics of a Fe : ZnSe laser operating in pulsed and repetitively pulsed regimes are studied at room temperature of the polycrystalline active element. The crystal was pumped by a nonchain electric-discharge HF laser. The energy of the Fe : ZnSe laser in a single-pulse regime was 1.67 J at the slope efficiency with respect to the absorbed and incident energy of ∼43% and ∼27%, respectively. In a repetitively pulsed regime with a pulse repetition rate of 20 Hz and an efficiency with respect to the absorbed power of ∼40%, the average laser power was ∼20 W with an individual pulse energy of ∼1 J. The possibility of increasing the average power of the repetitively pulsed Fe : ZnSe laser at room temperature is discussed.